PURIFICATION OF WATER SOLUBLE PROTEINS (2S ALBUMINS) EXTRACTED FROM PEANUT DEFATTED FLOUR AND ISOLATION OF THEIR ISOFORMS BY GEL FILTRATION AND ANION EXCHANGE CHROMATOGRAPHY - IMÈNE BOUALEG; AISSA BOUTEBBA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
2S albumins are water-soluble seed storage proteins present in dicotyledonous plants, including legumes. In peanuts, 2S albumins have been identified as major allergens. In this work, we aimed to study these water soluble allergenic proteins. They were extracted in water from peanut defatted flour (oilcake). It was quantified by Bradford method. The total and insoluble proteins content was determined by Kjeldahl method (% P = N x 6.25). The crude 2S albumins were purified using gel-filtration chromatography. Anion exchange chromatography analysis was applied to isolate their isoforms. The recorded values for total and insoluble proteins are 45.49 % and 36.65 % consecutively. A value of 9.99 % was determined for water soluble proteins content which correspond to 20 % compared to the total proteins. Analysis by Sephadex G-75 chromatography of soluble extract gave two majors peaks in which, the Mr ~ 25 kDa peak was predicted to be pure 2S albumin fraction. Using DAEA-cellulose chromatography, two peaks were appeared from pure 2S albumins, it were predicted that 2S albumin isoforms theoretically represent the peanut major allergens Ara h2 and Ara h6. These approaches are the basis for further studies may involve immunological analysis to understand the impact of these biomolecules on peanut allergenicity.